NEW INSIGHTS INTO THE ETIOPATHOGENESIS OF TYPE 1 DIABETES MELLITUS - Kudratova Z.E; Shamsiddinova D.K (Western European Studies, 2024)
Diabetes mellitus (DM) is a large group of complex metabolic diseases characterized by chronic hyperglycemia due to impaired insulin secretion or action, or a combination of these disorders [1]. Disruption of insulin secretion and/or decreased tissue response to insulin as part of complex hormonal processes leads to impaired insulin action on target tissues, which in turn causes disturbances in carbohydrate, fat, and protein metabolism. Impaired insulin secretion and impaired insulin action can occur simultaneously in the same patient. Type 1 diabetes (DM 1) is an autoimmune disease in genetically predisposed individuals in which chronic lymphocytic insulitis leads to T-cell-mediated destruction of β-cells with the subsequent development of absolute insulin deficiency, with a propensity to develop diabetic ketoacidosis (DKA). DM 1 is characterized by chronic, immune-mediated destruction of pancreatic islet βcells, which leads in most cases to absolute insulin deficiency. The destruction of β-cells occurs at different rates and becomes clinically significant when approximately 90% of β-cells are destroyed. DM 1 is a multifactorial disease, but the specific mechanisms of interaction between genetic predisposition, environmental factors, and the immune system underlying DM 1 remain unclear
Keywords: predisposition; interaction; environmental; immune system